Does environmental regulation affect global value chain position in service sectors? Evidence from 41 major economies - Liu, Huiqun; Chen, Lixin; Shan, Yibing (Frontiers in Environmental Science, 2022)
The increasing international division of production and the stringent environmental policies coexist, which lets people focus more on the research on the relationship between environmental regulation and global value chain (GVC). Based on the characteristics of service sectors, this paper poses hypotheses of how environmental regulation affects GVC position in service sectors and empirically investigates it by using panel data of GVC position index in service sectors and environmental performance index (EPI) from selected 41 major economies during 2006-2014. Our empirical study finds: firstly, environmental regulation has significantly promoted the increase of GVC position in service sectors, which obviously can verify the validity of the Porter Hypothesis. Secondly, environmental health has a greater effect on GVC position in service sectors than ecosystem vitality. Thirdly, the influence of environmental regulation on GVC position in service sectors is heterogeneous under different quantiles. The higher per capita income, the more stringent their environmental regulation and the stronger their impact on GVC position in service sectors are. In general, this study will contribute to a better understanding of the relationship between environmental regulation and GVC.